Abstracts of the 20th Annual Meeting of the German Society for Radiation Oncology (DEGRO), 3-4 July, 2014, Dusseldorf, Germany 20. Jahrestagung der Deutschen Gesellschaft für Radioonkologie - Deloch, Lisa; Derer, Anja; Rühle, Paul-Friedrich; Ott, Oliver; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2014)
Created from Fastlane, Scopus look-up

Analysis of the immune status from peripheral whole blood with a single-tube multicolor flow cytometry assay - Donaubauer, Anna-Jasmina; Becker, Ina; Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Methods in Enzymology, 2020)
Supplementation of standard cancer therapies (radiotherapy, chemotherapy, surgery) with immunotherapies has revolutionized cancer treatment. In order to include recent improvements of multimodal therapies into clinical routine, knowledge about the immune status, the immune dynamics and the detailed composition and activation of patient's immune system is required. The here presented single-tube multicolor flow cytometry assay allows the discrimination of 20 clinically relevant immune cell subsets and their activation status in peripheral whole blood. It includes 15 different antibodies and can be established on a common 3 laser and 10 color flow-cytometer. Furthermore, this assay is easy to set-up and to perform as well as fast with only 40 min of sample preparation time. Moreover, only 100 μL of whole blood are sufficient for this precise determination of the individual immune status. It is already applied in translational programs of clinical studies and trials and can further be adapted for future ones.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Immune status; Immunophenotyping; Multicolor flow-cytometry; Peripheral whole blood; Radioimmunotherapies

Clinically Relevant Radiation Exposure Differentially Impacts Forms of Cell Death in Human Cells of the Innate and Adaptive Immune System - Falcke, Sylvia; Rühle, Paul-Friedrich; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (International Journal of Molecular Sciences, 2018)
In cancer treatments, especially high-dose radiotherapy (HDRT) is applied. Patients suffering from chronic inflammatory diseases benefit from low-dose radiation therapy (LDRT), but exposure to very low radiation doses can still steadily increase for diagnostic purposes. Yet, little is known about how radiation impacts on forms of cell death in human immune cells. In this study, the radiosensitivity of human immune cells of the peripheral blood was examined in a dose range from 0.01 to 60 Gy with regard to induction of apoptosis, primary necrosis, and secondary necrosis. Results showed that immune cells differed in their radiosensitivity, with monocytes being the most radioresistant. T cells mainly died by necrosis and were moderately radiosensitive. This was followed by B and natural killer (NK) cells, which died mainly by apoptosis. X-radiation had no impact on cell death in immune cells at very low doses (≤0.1 Gy). Radiation doses of LDRT (0.3⁻0.7 Gy) impacted on the more radiosensitive NK and B cells, which might contribute to attenuation of inflammation. Even single doses applied during RT of tumors did not erase the immune cells completely. These in vitro studies can be considered as the basis to optimize individual radiation therapy schemes in multimodal settings and to define suited time points for further inclusion of immunotherapies.
EVALuna2:36450

Development of a Modular Assay for Detailed Immunophenotyping of Peripheral Human Whole Blood Samples by Multicolor Flow Cytometry - Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (International Journal of Molecular Sciences, 2016)
The monitoring of immune cells gained great significance in prognosis and prediction of therapy responses. For analyzing blood samples, the multicolor flow cytometry has become the method of choice as it combines high specificity on single cell level with multiple parameters and high throughput. Here, we present a modular assay for the detailed immunophenotyping of blood (DIoB) that was optimized for an easy and direct application in whole blood samples. The DIoB assay characterizes 34 immune cell subsets that circulate the peripheral blood including all major immune cells such as T cells, B cells, natural killer (NK) cells, monocytes, dendritic cells (DCs), neutrophils, eosinophils, and basophils. In addition, it evaluates their functional state and a few non-leukocytes that also have been associated with the outcome of cancer therapy. This DIoB assay allows a longitudinal and close-meshed monitoring of a detailed immune status in patients requiring only 2.0 mL of peripheral blood and it is not restricted to peripheral blood mononuclear cells. It is currently applied for the immune monitoring of patients with glioblastoma multiforme (IMMO-GLIO-01 trial, NCT02022384), pancreatic cancer (CONKO-007 trial, NCT01827553), and head and neck cancer (DIREKHT trial, NCT02528955) and might pave the way for immune biomarker identification for prediction and prognosis of therapy outcome.
EVALuna2:18363

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Erratum to: Primary glioblastoma multiforme tumors and recurrence: comparative analysis of the danger signals HMGB1, HSP70, and calreticulin - Muth, Carolin; Rubner, Yvonne; Semrau, Sabine; Rühle, Paul-Friedrich; Frey, Benjamin; Strnad, Annedore; Buslei, Rolf; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2016)
EVALuna2:7315

GLIO-CMV-01: Identification of immune biomarkers for CMV-related encephalitis during radiotherapy of the brain - Donaubauer, Anna-Jasmina; Becker, I.; Rühle, Paul-Friedrich; Goerig, Nicole; Pohn, A.; Winkler, Thomas; Korn, Klaus; Überla, Klaus; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36498

GLIO-CMV-01: Identification of immune biomarkers for CMV related encephalitis during standard brain radiotherapy - Rühle, Paul-Friedrich; Goerig, Nicole; Korn, Klaus; Überla, Klaus; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32892

IMMO-LDRT01: Immunophenotyping of patients suffering from chronic degenerative joint diseases and receiving local low-dose radiation therapy - Harrer, A.; Rühle, Paul-Friedrich; Gryc, Thomas; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32884

Immune modulation by low dose radiation therapy-results from 70 patients followed up in the IMMO-LDRT01 study - Donaubauer, Anna-Jasmina; Gryc, Thomas; Becker, I.; Harrer, A.; Rühle, Paul-Friedrich; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36497

Immunological Aspects of intraoperative Radiotherapy in Breast Cancer after breast conserving Surgery - Tiefenthaller, A.; Brix, N.; Escudero, Pazos M.; Kost, B.; Rack, B.; Bodungen Von; Weissenbacher, T.; Wuerstlein, R.; Rühle, Paul-Friedrich; Gaipl, Udo; Harbeck, N.; Belka, C.; et al. (2017)
EVALuna2:32928

Immunomodulation by ionizing radiation-impact for design of radio-immunotherapies and for treatment of inflammatory diseases - Frey, Benjamin; Rueckert, Michael; Rühle, Paul-Friedrich; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Immunological Reviews, 2017)
Ionizing radiation is often regarded as an element of danger. But, danger responses on the cellular and molecular level are often beneficial with regard to the induction of anti-tumor immunity and for amelioration of inflammation. We outline how in dependence of radiation dose and fraction, radiation itself-and especially in combination with immune modulators-impacts on the innate and adaptive immune system. Focus is set on radiation-induced changes of the tumor cell phenotype and the cellular microenvironment including immunogenic cancer cell death. Mechanisms how anti-tumor immune responses are triggered by radiotherapy in combination with hyperthermia, inhibition of apoptosis, the adjuvant AnnexinA5, or vaccination with high hydrostatic pressure-killed autologous tumor cells are discussed. Building on this, feasible multimodal radio-immunotherapy concepts are reviewed including overcoming immune suppression by immune checkpoint inhibitors and by targeting TGF-β. Since radiation-induced tissue damage, inflammation, and anti-tumor immune responses are interconnected, the impact of lower doses of radiation on amelioration of inflammation is outlined. Closely meshed immune monitoring concepts based on the liquid biopsy blood are suggested for prognosis and prediction of cancer and non-cancer inflammatory diseases. Finally, challenges and visions for the design of cancer radio-immunotherapies and for treatment of benign inflammatory diseases are given.
EVALuna2:32867

Impact of radon and combinatory radon/carbon dioxide spa on pain and hypertension: Results from the explorative RAD-ON01 study - Rühle, Paul-Friedrich; Klein, Gerhart; Rung, Tatiana; Phan, Hong Tiep; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Modern Rheumatology, 2019)
OBJECTIVES: Therapies with low doses of radon have beneficial effects on patients suffering from chronic painful degenerative and inflammatory diseases. We already showed that this is accompanied by systemic immune modulations. We here focus on pain-reducing effects of very low doses of radon by adding carbon dioxide water and its impact on heart rate variability (HRV), blood pressure and free radicals. METHODS: 97 of 103 patients receiving radon spa (1.200 Bq/l at 34 °C or 600 Bq/l, 1 g/l CO2 at 34 °C) were monitored before and at three different time points after therapy. Individual pain perception was analyzed and the capability to process radicals. At each time point, the hypertensive patients (n = 46) were examined over 24 h for blood pressure and HRV. RESULTS: Long-term pain reduction was observed in the majority of patients. A modulation of superoxide dismutase was identified, presumably representing a priming effect for lowering radiation stress. Further, lowering of blood pressure, especially in those patients who additionally received carbon dioxide, was seen. Radon did in particular impact on HRV implying lasting relaxation effects. CONCLUSION: Radon/carbon dioxide spa efficiently reduces pain. In particular, patients simultaneously suffering from painful and cardiovascular diseases should be treated by combination of radon and CO2.
EVALuna2:36466

Interconnection between DNA damage, senescence, inflammation, and cancer - Wunderlich, Roland; Rühle, Paul-Friedrich; Unger, Kristian; Hess, Julia; Zitzelsberger, Horst; Lauber, Kirsten; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Frontiers in Bioscience, 2017)
In order to deal with endogenous and exogenous factors, including radiation or pathogens, cells evolved different strategies. This includes highly complex processes such as DNA damage response, senescence, cell death, and inflammatory reactions. Recent research indicates an interconnection between the mentioned cellular pathways whilst all of them seem to play a role in induction and progression, but also the prevention of cancerous diseases and therefore qualify for potential prevention and treatment strategies. On the basis of their pivotal functions in cancer biology in general, each of the cellular processes represents promising single therapeutic targets. Further, due to their strong interconnection, targeting all of them in a multimodal approach could be another promising strategy to treat cancer. We, therefore, review the mechanisms of DNA damage induction, detection and repair as well as the induction of cell death. Further, features of senescence and mechanism of inflammation induction and abrogation are outlined. A special focus is set on how senescence and inflammation are related to diseases and how targeting them could contribute to improvement of cancer therapies.
EVALuna2:33313

Ionizing radiation reduces the capacity of activated macrophages to induce T-cell proliferation, but does not trigger dendritic cell-mediated non-targeted effects - Wunderlich, Roland; Rühle, Paul-Friedrich; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (International Journal of Radiation Biology, 2019)
PURPOSE: Previous investigations revealed influences of irradiation up to 2Gy on the cytokine secretion profile of inflammatory and peritoneal mouse macrophages (pMФ). This raised the question if those alterations impact on dendritic cells and consecutive T-cell responses. Further, the impact of irradiation directly on pMФ capacity to induce T-cell responses was analyzed. MATERIALS AND METHODS: pMФ were LPS-activated, irradiated and the expression of activation markers was assessed. Treated pMФ were co-incubated with T-cells to investigate proliferation. To verify modulating properties of pMФ supernatants isolated 24 h after irradiation, bone marrow-derived dendritic cells (BMDC) were co-incubated with supernatants and activation markers as well as the BMDC-induced proliferation of T-cells were measured. RESULTS: pMФ showed a highly significantly decreased major histocompatibility complexII (MHCII) expression within a dose range from 0.7-2Gy. Further, the proliferation rate of cluster of differentiation 4+ (CD4+) T-cells was decreased after co-incubation particularly with 2 Gy irradiated pMФ. The co-incubation of BMDC with supernatants of activated, irradiated pMФ significantly reduced the CD40 expression, but did not impact on the BMDC-derived induction of T-cell proliferation. CONCLUSIONS: Inflammatory macrophages being exposed to irradiation have the potential to modulate consecutive adaptive immune reactions. But supernatants of irradiated macrophages do not influence the dendritic cells (DC)-mediated induction of T cell proliferation.
EVALuna2:36459

Local and systemic immunological Effects of intraoperative Radiotherapy (IORT) for Breast Cancer - Tiefenthaller, A.; Brix, N.; Hennel, R.; Pazos, M.; Kost, B.; Rack, B.; Von Bodungen; Weissenbacher, T.; Wuerstlein, R.; Rühle, Paul-Friedrich; Gaipl, Udo; Harbeck, N.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Low-Dose Radiotherapy Ameliorates Advanced Arthritis in hTNF-α tg Mice by Particularly Positively Impacting on Bone Metabolism - Deloch, Lisa; Derer, Anja; Hueber, Axel; Herrmann, Martin; Schett, Georg; Wölfelschneider, Jens; Hahn, Jonas; Rühle, Paul-Friedrich; Stillkrieg, Willy; Fuchs, Jana; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2018)
Inflammation and bone erosion are central in rheumatoid arthritis (RA). Even though effective medications for control and treatment of RA are available, remission is only seen in a subset of patients. Treatment with low-dose radiotherapy (LD-RT) which has been already successfully used for amelioration of symptoms in benign diseases should be a promising approach to reduce pain, inflammation, and particularly bone erosion in patients with RA. Even though anti-inflammatory effects of LD-RT are already described with non-linear dose response relationships, and pain-reducing effects have been clinically observed, the underlying mechanisms are widely unknown. Besides immune cells many other cell types, such as fibroblast-like synoviocytes (FLS), osteoclasts, and osteoblast are present in the affected joint and might be modulated by LD-RT. For this study, these cell types were obtained from human tumor necrosis factor-α transgenic (hTNF-α tg) mice and were consecutively exposed to different doses of ionizing radiation (0.1, 0.5, 1.0, and 2.0 Gy, respectively) in vitro. In order to study the in vivo effects of LD-RT within the arthritic joint, hind paws of arthritic hTNF-α tg mice were locally irradiated with 0.5 Gy, a single dose per fraction that is known for good clinical responses. Starting at a dose of 0.5 Gy, proliferation of FLS was reduced and apoptosis significantly enhanced with no changes in necrosis. Further, expression of RANK-L was slightly reduced following irradiation with particularly 0.5 Gy. Starting from 0.5 Gy, the numbers of differentiated osteoclasts were significantly reduced, and a lower bone resorbing activity of treated osteoclasts was also observed, as monitored via pit formation and Cross Laps presence. LD-RT had further a positive effect on osteoblast-induced mineralization in a discontinuous dose response relationship with 0.5 Gy being most efficient. An increase of the gene expression ratio of OPG/RANK-L at 0.1 and 0.5 Gy and of production of OPG at 0.5 and 1.0 Gy was observed. In vivo, LD-RT resulted in less severe arthritis in arthritic hTNF-α tg mice and in significant reduction of inflammatory and erosive area with reduced osteoclasts and neutrophils. Locally applied LD-RT can, therefore, induce a beneficial micro-environment within arthritic joints by predominantly positively impacting on bone metabolism.
EVALuna2:34663
Keywords: rheumatoid arthritis; inflammation; low-dose radiotherapy; bone metabolism; synovial-like fibroblasts; osteoclasts; osteoblasts

Modulation of the peripheral immune system after low-dose radon spa therapy: Detailed longitudinal immune monitoring of patients within the RAD-ON01 study - Rühle, Paul-Friedrich; Wunderlich, Roland; Fournier, Claudia; Maier, Andreas; Klein, Gerhart; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (Autoimmunity, 2017)
The pain-relieving effects of low-dose radon therapies on patients suffering from chronic painful inflammatory diseases have been described for centuries. Even though it has been suggested that low doses of radiation may attenuate chronic inflammation, the underlying mechanisms remain elusive. Thus, the RAD-ON01 study was initiated to examine the effects of radon spa therapy and its low doses of alpha radiation on the human immune system. In addition to an evaluation of pain parameters, blood was drawn from 100 patients suffering from chronic painful degenerative musculoskeletal diseases before as well as 6, 12, 18, and 30 weeks after the start of therapy. We verified significant long-term pain reduction for the majority of patients which was accompanied by modulations of the peripheral immune cells. Detailed immune monitoring was performed using a multicolor flow cytometry-based whole blood assay. After therapy, the major immune cells were only marginally affected. Nevertheless, a small but long-lasting increase in T cells and monocytes was observed. Moreover, neutrophils, eosinophils and, in particular, dendritic cells were temporarily modulated after therapy. Regarding the immune cell subsets, cytotoxic T and NK cells, in particular, were altered. However, the most prominent effects were identified in a strong reduction of the activation marker CD69 on T, B, and NK cells. Simultaneously, the percentage of HLA-DR+T cells was elevated after therapy. The RAD-ON01 study showed for the first time a modulation of the peripheral immune cells following standard radon spa therapy. These modulations are in line with attenuation of inflammation.
EVALuna2:32908

Modulations in the Peripheral Immune System of Glioblastoma Patient Is Connected to Therapy and Tumor Progression-A Case Report from the IMMO-GLIO-01 Trial - Rühle, Paul-Friedrich; Goerig, Nicole; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Strnad, Annedore; Frey, Benjamin (Frontiers in Neurology, 2017)
Immune responses are important for efficient tumor elimination, also in immune privileged organs such as the brain. Fostering antitumor immunity has therefore become an important challenge in cancer therapy. This cannot only be achieved by immunotherapies as already standard treatments such as radiotherapy and chemotherapy modify the immune system. Consequently, the understanding of how the tumor, the tumor microenvironment, and immune system are modulated by cancer therapy is required for prognosis, prediction, and therapy adaption. The prospective, explorative, and observational IMMO-GLIO-01 trial was initiated to examine the detailed immune status and its modulation of about 50 patients suffering from primary glioblastoma multiforme (GBM) or anaplastic astrocytoma during standard therapy. Prior to the study, a flow cytometry-based assay was established allowing the analysis of 34 immune cell subsets and their activation state. Here, we present the case of the first and longest accompanied patient, a 53-year-old woman suffering from GBM in the front left lobe. In context of tumor progression and therapy, we describe the modulation of the peripheral immune status over 17 months. Distinct immune modulations that were connected to therapy response or tumor progression were identified.Inter alia, a shift of CD4:CD8 ratio was observed that correlated with tumor progression. Twice we observed a unique composition of peripheral immune cells that correlated with tumor progression. Thus, following up these immune modulations in a closely-meshed manner is of high prognostic and predictive relevance for supporting personalized therapy and increasing therapy success.Clinical Trial registration: ClinicalTrials.gov, identifier NCT02022384 (registered retrospectively on 13th of December, 2013).
EVALuna2:32874

One-tube multicolor flow cytometry assay (OTMA) for comprehensive immunophenotyping of peripheral blood - Donaubauer, Anna-Jasmina; Rühle, Paul-Friedrich; Becker, Ina; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Human Monoclonal Antibodies, 2019)
Recent improvements in the flow cytometry technology allow the determination of the general immune status through the development of multicolor immunofluorescence panels. The one-tube multicolor flow cytometry assay (OTMA) that is presented here identifies 20 different, clinically relevant immune cell subsets and three common activation markers. Thereby, a comprehensive immune status that covers all major immune cells is easily obtained. The assay is suitable for every common three lasers and 10 color flow cytometer and includes the application of 15 different antibodies. Furthermore, the assay requires only 100 μL of EDTA-treated whole-blood and less than 40 min for sample preparation. By being easily adaptable to individual requirements and by additionally determining absolute cell counts, the assay is well-suited for translational research in clinical trials.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Absolute cell count; Antibody; Gating strategy; Human whole-blood; Immune status; Immunophenotyping; Multicolor flow cytometry; One-tube measurement

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

Primary glioblastoma multiforme tumors and recurrence : Comparative analysis of the danger signals HMGB1, HSP70, and calreticulin - Muth, Carolin; Ruebner, Yvonne; Semrau, Sabine; Rühle, Paul-Friedrich; Frey, Benjamin; Strnad, Annedore; Buslei, Rolf; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2016)
Glioblastoma multiforme (GBM) is the most common and aggressive brain tumor. Despite improved multimodal therapies, the tumor recurs in most cases. Diverging patient survival suggests great tumor heterogeneity and different therapy responses. Danger signals such as high-mobility group box protein 1 (HMGB1), heat shock protein 70 (HSP70), and calreticulin (CRT) are biomarker candidates, due to their association with tumor progression versus induction of antitumor immune responses. Overexpression of these danger signals has been reported for various types of tumors; however, their role in GBM is still elusive. A direct comparison of their expression in the primary tumor versus the corresponding relapse is still lacking for most tumor entities.We therefore performed an expression analysis by immunohistochemistry of the danger signals HMGB1, HSP70, and CRT in primary tumors and the corresponding relapses of 9 patients with de novo GBM.HMGB1 was highly expressed in primary tumors with a significant reduction in the respective relapse. The extracellular HSP70 expression was significantly increased in the relapse compared to the primary tumor. CRT was generally highly expressed in the primary tumor, with a slight increase in the relapse.The combination of a decreased expression of HMGB1, an increased expression of extracellular HSP70, and an increased expression of CRT in the relapse seems to be beneficial for patient survival. HMGB1, extracellular HSP70, and CRT could be taken into concerted consideration as potential biomarkers for the prognosis of patients with GBM.
EVALuna2:7316

RAD-ON01 study: modulation of the peripheral immune system following a sequential radon spa therapy - Rühle, Paul-Friedrich; Kullmann, M.; Frey, Benjamin; Klein, G.; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32893

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Temporarily increased TGFβ following radon spa correlates with reduced pain while serum IL-18 is a general predictive marker for pain sensitivity - Kullmann, Miriam; Rühle, Paul-Friedrich; Harrer, Alexandra; Donaubauer, Anna-Jasmina; Becker, Ina; Sieber, Renate; Klein, Gerhart; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Radiation and Environmental Biophysics, 2019)
Sustained pain relief following radon spa therapy in patients suffering from chronic painful diseases has been well described. But still, the underlying mechanisms are not fully understood. We conducted the prospective and explorative RAD-ON01 study which included 103 patients who suffered from chronic painful musculoskeletal disorders of the spine and/or joints and present here the data of the examination of pro- and anti-inflammatory cytokines in the serum of the patients before and at weeks 6, 12 and 30 after therapy. While TNFα, IL-1β, IFNγ, IL-1Ra and IL-10 were not altered, TGFβ was temporarily significantly (p = 0.013) elevated 6 weeks after therapy. Importantly, this elevation positively correlated with lowered pain sensitivity (r = 0.41). Further, the amount of IL-18 in the serum positively correlated with lowered pain sensitivity. Therefore, IL-18 can be considered as predictive marker for pain sensitivity of radon spa patients. We conclude that alterations in TGFβ and general IL-18 levels in serum have prognostic and predictive value in situations of lowered pain by exposure of patients to very low-doses of radiation as it is the case in radon spa.
EVALuna2:36449